The goal of full employment - Gordon, Robert Aaron (New York : Wiley, 1967)
In this book, which is merely a part of the output of a research program on Unemployment and the American Economy being carried on at the Institute of Industrial Relations at Berkeley, Gordon tackles several very important problems and gives a masterful performance.
"One of a series of books from the Research Program on Unemployment, Institute of Industrial Relations, University of California, Berkeley."
Includes bibliographical references.
rpm 12/04/2018
Loans
Keywords: Full employment policies